Peran Tasawuf Di Era Masyarakat Modern "Peluang dan Tantangan” - Ghulam Falach; Ridhatullah Assya’bani (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2021)
This paper will dissect the role of Sufism in the era of modern society. The era of modernity with all its advances, from the outward side, is sufficient for the life of modern society, while from the spiritual side of modern society there is still a drought of spiritual values, such as the loss of morals, mismatches in the application of science and technology, the decline in the quality of faith, individualistic and materialistic attitudes can be resolved with Sufism with using the method. Until now, Sufism is believed to be able to solve various crises of modern society. Therefore Sufism can be used as a means and fulfillment of human needs from the spiritual side. This modernity has also generated industrialization, science, and technology, which have increasingly influenced life, resulting in a shift in patterns and lifestyles, where moral values, ethics, and teachings began to be abandoned because they were deemed incompatible with modern values. At this point, there is a crisis of existence and spiritual aridity. Through the implementation of Sufism in the modern era, it is very much needed by transforming the understanding of Sufism, not only maqamat and awhile, but modifying Sufism in such a way that it becomes dynamic and open so that it is easily understood and practiced by humans in modern times. Sufism as a means to get closer to God is expected to be able to overcome the spiritual crisis because with its values Sufism can provide a balance in human life. From the results of the analysis, it can be seen that Sufism has a breath of fresh air to overcome the various problems of modern society and to balance between lahiriyah and batiniyah. Also, Sufism becomes important for the life of modern society because Sufism can function as a controller and controller of humans so that the human dimension is not reduced by modernization that directs humans to anomalous values so that it will lead humans to the achievement of moral superiority.